Menggunjing Relief Candi Borobudur sebagai “Cikal Bakal” Komik Indonesia - Aditya Nirwana (Program Studi Desain Komunikasi Visual, Fakultas Sains dan Teknologi, Universitas Ma Chung, 2020)
Referring to the study of Indonesian Comics, most of the critics and researchers agreed on Indonesia's first comic is Put On, (Kho Wan Gie), published in the 1930s in Sin Po Daily in the form of humorous strip comic medium. Most consider the reliefs of the Borobudur temple, wayang beber, and wayang kulit as